Regularities of Organometric Characteristics of Cerebellum in Young and old Age - Irina A Balandina (Journal of Global Pharma Technology, 2017)
Background: The interest in morphological studies of cerebellum in different periods of postnatalontogenesis is steadily increasing. The most acute lack of age anatomy data exists for elderly patients.Since the information on structural peculiarities of cerebellum and its cortex at old age is poorlyrepresented in literature, being also contradictory in many ways, the study underlying the current paperwas dedicated to this issue. Aims: The purpose of the study was to find regularities of age-relatedchanges in organometric parameters of cerebellum and structural organization of its cortex at old age ascompared to the young age at old age as using necropsy material. Methods: The paper is based onmorphological study of cerebellums of 219 human corpses (108 male and 111 female) of young and oldages using organometric, histological and morphometric research methods. The study includedcomparative analysis of the mass, linear dimensions, thickness of the cerebellar cortex in young and oldages. Results: The regularities of age variability of organometric characteristics of cerebellum wereidentified, manifested in reduction of its weight and linear dimensions in people of senile age comparedto younger people. It was found that the thickness of molecular and granular layer of cerebellum ischaracterized by age-related decrease in parameters. Conclusions: The results of this morphologicalstudy can serve as a basis for identifying specific regularities of age anatomy of cerebellum and havepractical significance as standard indicators, which will allow using these data for diagnostic andtherapeutic purposes.